Determinants of Discordance Between Criteria for Inactive Disease and Low Disease Activity in Juvenile Idiopathic Arthritis. Issue 12 (11th October 2021) - Giancane, Gabriella; Campone, Chiara; Gicchino, Maria Francesca; Alongi, Alessandra; Bava, Cecilia; Rosina, Silvia; Boyko, Yaryna; Martin, Neil; El Miedany, Yasser; Harjacek, Miroslav; Hashad, Soad; Ioseliani, Maka; et al.
Abstract : Objective: To assess concordance among criteria for inactive disease (ID) and low disease activity (LDA) in juvenile idiopathic arthritis (JIA) and to seek factors driving discordance. Methods: The frequency of fulfillment of existing criteria was evaluated in information on 10, 186 patients extracted from 3 cross‐sectional data sets. Patients were divided up according to the functional phenotypes of oligoarthritis and polyarthritis. Concordance between criteria was examined using weighted Venn diagrams. The role of each individual component in explaining discordance between criteria was assessed by calculating the absolute number and percentage of instances in which the component was responsible for discrepancy between definitions. Results: Criteria for ID were met by 28.6–41.1% of patients with oligoarthritis and by 24.0–33.4% of patients with polyarthritis. Criteria for LDA were met by 44.8–62.4% of patients with oligoarthritis and by 44.6–50.4% of patients with polyarthritis. There was a 57.9–62.3% overlap between criteria for ID and a 67.9–85% overlap between criteria for LDA. Parent and physician global assessments and acute‐phase reactants were responsible for the majority of instances of discordance among criteria for ID (8.7–15.5%, 10.0–12.3%, and 10.8–17.3%, respectively). Conclusion: We found fair concordance between criteria for ID and LDA in JIA, with the main drivers of discordance for ID being physician and parent global assessments and acute‐phase reactants. This observation highlights the need for further studies aimed to evaluate the impact of subjective physician and parent perception of disease remission and of laboratory measures of inflammatory activity on the definition of ID.